Hunting for right and left parietal hot spots using single-pulse TMS: modulation of visuospatial perception during line bisection judgment in the healthy brain - Salatino, Adriana; Poncini, Marisa; George, Mark S.; Ricci, Raffaella (Frontiers in Psychology, 2014)
A series of studies have consistently reproduced left neglect-like bias on line length estimation tasks in healthy participants by applying TMS over the right Posterior Parietal Cortex (PPC), while no significant changes have been reported when stimulating the left PPC. However, a notable inter-individual variability in the right parietal site where TMS modulates visuospatial perception can be observed, and no general agreement exists on how to identify the optimal parietal site of stimulation. In the present study, we propose a new site-finding TMS protocol to easily identify the optimum parietal location, or ‘hot spot’, where TMS may modulate visuospatial perception on a line length estimation task (the Landmark task). Single-pulse TMS at 115% of motor threshold was applied 150 ms after the visual stimulus onset over nine different sites of a 3 by 3 cm grid, centred over right or left PPC (P4 and P3 according to the 10-20 EEG system, respectively) in eight healthy participants. Stimulation of right PPC induced a significant left neglect-like bias, when the coil was applied over the most posterior and dorso-posterior sites. Unexpectedly, TMS over left PPC also produced left neglect-like bias. However, in this case significant effects were found when targeting the most anterior and dorso-anterior portions of the grid. These results are discussed in relation to recent findings on neural networks underlying spatial cognition. The hunting protocol we propose might offer an economical and easy-to-use tool to functionally identify the optimal parietal site where TMS can modulate visuospatial perception, in healthy subjects and possibly in post-stroke patients undergoing rTMS treatment.